Oral isotretinoin induced giant lobular capillary haemangioma over scalp: a rare case report - Khan, Shafaq; Pathak, Prateek; Kulhari, Monika; Singh, P. K. (International Journal of Research in Dermatology, 2023)
With the advent of isotretinoin in the last 2 decades, dermatotheraputics has reached a major milestone especially in treating moderate to severe acne. Oral isotretinoin is an isomer of all-trans retinoic acid and a metabolite of retinol (vitamin A). In addition to its excellent response in moderate to severe acne, there are a number of well-documented side effects related to the use of isotretinoin. Lobular capillary haemangioma is a very rare side effect. It is sometimes known as granuloma pyogenicum and it is an acquired, benign vascular tumor that arises in tissues such as the skin and mucous membranes. Herein, we report a case of isotretinoin-induced lobular capillary hemangioma over the scalp (an atypical site).